TENAYA and LUCERNE - Arshad M. Khanani, MD, MA; Robyn H. Guymer, MD, PhD; Karen Basu, PhD; Heather Boston, MSc; Jeffrey S. Heier, MD; Jean-François Korobelnik, MD; Aachal Kotecha, PhD; Hugh Lin, MD, MBA; David Silverman, MBChB, MRCOphth; Balakumar Swaminathan, MSc; Jeffrey R. Willis, MD, PhD; Young Hee Yoon, MD, PhD; et al. (Ophthalmology Science, 2021)
Purpose: To describe the design and rationale of the phase 3 TENAYA (ClinicalTrials.gov identifier, NCT03823287) and LUCERNE (ClinicalTrials.gov identifier, NCT03823300) trials that aimed to assess efficacy, safety, and durability of faricimab, the first bispecific antibody for intraocular use, which independently binds and neutralizes both angiopoietin-2 and vascular endothelial growth factor-A (VEGF-A) versus aflibercept in patients with neovascular age-related macular degeneration (nAMD). Design: Identical, global, double-masked, randomized, controlled, phase 3 clinical trials. Participants: Adults with treatment-naïve nAMD. Methods: These trials were designed to evaluate patients randomized to receive faricimab 6.0 mg up to every 16 weeks after 4 initial every-4-week doses or aflibercept 2.0 mg every 8 weeks after 3 initial every-4-week doses. The initial doses in the faricimab arm were followed by individualized fixed treatment intervals up to week 60, based on disease activity assessment at weeks 20 and 24, guided by central subfield thickness, best-corrected visual acuity (BCVA), and investigator assessment. The primary efficacy end point was BCVA change from baseline averaged over weeks 40, 44, and 48. Secondary end points included the proportion of patients receiving every-8-week, every-12-week, and every-16-week faricimab and anatomic outcomes. Safety outcomes included incidence and severity of ocular and nonocular adverse events. From week 60, faricimab-treated patients followed a personalized treatment interval (PTI), a novel protocol-driven treat-and-extend regimen with interval adjustment from every 8 weeks to every 16 weeks based on individualized treatment response measured by anatomic criteria, functional criteria, and investigator assessment of patients’ disease activity. Main Outcome Measures: Rationale for trial design and PTI approach. Results: The TENAYA and LUCERNE trials were the first registrational trials in nAMD to test fixed dosing regimens up to every 16 weeks based on patients' disease activity in year 1 and incorporate a PTI paradigm during year 2. The PTI approach was designed to tailor treatment intervals to individual patient needs, to reflect clinical practice treatment practice, and to reduce treatment burden. Conclusions: The innovative trial design rationale for the TENAYA and LUCERNE trials included maximizing the benefits of angiopoietin-2 blockade through dosing up to every 16 weeks and PTI regimens based on patients' disease activity while fulfilling health authority requirements for potential registrational efforts.